(untitled) (Bangladesh Agronomy Journal, 2020)
Crop and nutrient management options could improve the yield performances of late transplant Aman rice which is generally lower compared to optimum transplanting. To address these issues, an experiment was conducted at Bangladesh Agricultural University, Mymensingh to investigate the effect of spacing and nutrient management options on yield and yield components of late transplant Aman rice and to find out the better treatment combination to obtain higher yield. The experiment was laid out in two factors randomized complete block design (RCBD) with three replications consisting of three spacings viz. S1 =25 cm×15 cm , S2 =25 cm×10 cm and S3 =20 cm×10 cm; and eight nutrient management options viz. N0 = Control (No fertilizer), N1 = Poultry manure @ 5 t ha-1 , N2 = Vermicompost @ 3 t ha-1 , N3 = Researcher’s practice (Urea, TSP, MoP, Gypsum and ZnSO4 @ 180,75,105, 60 and 7.5 kg ha-1, respectively), N4 = 75% N3 + Poultry manure @ 2.5 t ha-1, N5 = 50% N3+ poultry manure @ 5 t ha-1, N6 = 75% N3+ Vermicompost @ 1.5 t ha-1 and N7 = 50% N3+ Vermicompost @ 3 t ha-1. Pre-germinated seeds of BRRI dhan46 were sown in wet nursery bed on 16 August and 30–d–old seedlings were transplanted as per treatments on 15 September in 2017. Yield and yield components were significantly influenced by spacing, nutrient management options and their interactions. The highest yield (5.20 t ha-1) was obtained the spacing 25 cm×10 cm which was at par with 25 cm×15 cm (5.12 t ha-1) and the lowest (4.88 t ha-1) was in 20 cm×10 cm. Statistically similar grain yield 5.85, 5.81 and 5.79 t ha-1 were produced in the treatments N3, N4 and N6, respectively. Grain yield increased in the treatments having combination of inorganic and organic nutrient, and also in the optimum inorganic fertilizers (researcher’s practice). The highest grain yield (5.98 t ha-1) was obtained in the interaction S2×N3 which was at par with S1 x N3, S1 x N4, S1 x N6, S2 x N4 and S2 x N6. Performances of sole organic fertilizers were not satisfactory level. Therefore, reduced amount (75%) of inorganic fertilizers combined with organic fertilizers (poultry manure 2.5 t ha-1 or vermicompost 1.5 t ha-1) along with closer spacing 25 cm×10 cm would be recommended to achieve better and sustainable yield performance of late transplant Aman rice cv. BRRI dhan46. Bangladesh Agron. J. 2020, 23(1): 1-11